The Influence of Historical Changes on the Input of Sports Culture Communication and the Psychological State of the Audience - Shuilian Cui, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study examines the impact of historical changes on the input of sports culture communication and the psychological state of the audience, using the theories of cultural change and cultural ecology as a foundation. In several villages, questionnaires were administered to senior citizens. The sample size for this study is 110, and empirical evidence is gathered using Smart PLS 4 and the structural equation model. The research has demonstrated in the literature that historical changes affect sports culture communication. In the meantime, this research has reported in the scholarly literature that historical changes affect the psychological state of the audience. The findings of this study are unquestionably novel to the literature and have advanced the theory about sports culture communication and audience psychological state. Additionally, the research has some practical implications that must be incorporated to implement sports culture effectively. The future directions of this research highlight the limitations of this study.